PRINCIPLES OF PHYSIOLOGICAL NUTRITION, MOTOR ACTIVITY AND REGULATION OF THE DIGESTIVE SYSTEM. DIGESTION IN THE ORAL CAVITY AND STOMACH (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the physiological foundations of human nutrition, focusing on the principles that ensure balanced nutrient intake and optimal metabolic functioning. Special attention is given to the motor activity of the digestive tract and the complex regulatory mechanisms that coordinate digestive processes. The physiological stages of digestion in the oral cavity and stomach are analyzed in detail, including enzymatic activity, neural and hormonal control, and mechanical transformations of food. The study integrates contemporary physiological concepts to demonstrate the interdependence between motor function, secretory processes, and nutrient assimilation.
Keywords: Physiological nutrition, digestive system, motor activity, oral digestion, gastric digestion, enzymatic processes, neurohumoral regulation, peristalsis, metabolism.